SWIR imaging using PbS QD photodiode array sensors - Chang, Sehwan; Jin, Junyoung; Kyhm, Jihoon; Park, Tae Hwan; Ahn, Jongtae; Park, Sung-Yul L.; Park, Suk In; Hwang, Do Kyung; CHOI, SANG SOO; Seong, Tae-Yeon; Song, Jin-Dong; Hwang, Gyu Weon (Optical Society of America, 2022)
We fabricated a 1 x 10 PbS QD photodiode array with multiple stacked QD layers with high-resolution patterning using a customized photolithographic process. The array showed the average responsivity of 5.54 x 10(-3) A/W and 1.20 x 10(-2) A/W at 0 V and -1 V under 1310- nm short-wavelength infrared (SWIR) illumination. The standard deviation of the pixel responsivity was under 10%, confirming the uniformity of the fabrication process. The response time was 2.2 +/- 0.13 ms, and the bandwidth was 159.1 Hz. A prototype 1310-nm SWIR imager demonstrated that the QD photodiode-based SWIR image sensor is a cost-effective and practical alternative for III-V SWIR image sensors. (C) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement